2015
DOI: 10.1016/j.intfin.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Does sovereign creditworthiness affect bank valuations in emerging markets?

Abstract: We analyse the impact of sovereign rating actions by S&P, Moody's and Fitch on bank valuations in emerging markets. We find strong evidence of a rating channel for the transmission of sovereign risk to bank valuations. Collateral and guarantee channels play JEL classification: G15; G21; G24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…Similarly, Caselli, Gandolfi, and Soana (2014 find evidence of significant bank losses following sovereign rating downgrades in the European market. Correa et al (2014) find that banks which are expected to receive government support demonstrate lower stock returns after a sovereign rating downgrade, while Williams, Alsakka and ap Gwilym (2015) show that S&P actions induce a significant impact on bank valuations in emerging markets. Further, BIS 2011emphasises that sovereign debt concerns push up banks' funding costs.…”
Section: Spillover Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Caselli, Gandolfi, and Soana (2014 find evidence of significant bank losses following sovereign rating downgrades in the European market. Correa et al (2014) find that banks which are expected to receive government support demonstrate lower stock returns after a sovereign rating downgrade, while Williams, Alsakka and ap Gwilym (2015) show that S&P actions induce a significant impact on bank valuations in emerging markets. Further, BIS 2011emphasises that sovereign debt concerns push up banks' funding costs.…”
Section: Spillover Channelsmentioning
confidence: 99%
“…Sovereign ratings are considered as a key factor determining bank ratings (e.g. Shen et al, 2012;Alsakka et al, 2014;Huang and Shen, 2015;Williams et al, 2015), while bank rating levels are included to control for the banks' financial conditions and creditworthiness (see Section 2.1 for further details). Variables describing bank size, profitability, asset quality, capital adequacy and liquidity are found to be significant in explaining bank ratings (e.g.…”
Section: Univariate Testsmentioning
confidence: 99%
“…Prior studies find that the stock prices of domestic banks decrease significantly upon negative sovereign rating announcements but have no significant reaction to positive ones, particularly in developed markets (Alsakka et al, 2014;Correa et al, 2014;Caselli et al, 2016). In regions with more serious information asymmetry, even positive sovereign rating announcements can have a significant positive impact on bank stocks (Williams et al, 2013(Williams et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The academic literature has shown that changes in sovereign debt ratings can impact financial markets. Most notably, negative sovereign rating actions have affected sovereign bond markets (Cantor and Packer 1996; Gande and Parsley 2005), sovereign credit default swaps (CDS) markets (Ismailescu and Kazemi 2010), equity markets (Kaminsky and Schmukler 2002; Brooks et al 2004; Ferreira and Gama 2007; Correa et al 2012, Williams et al 2015, Tran et al 2019), and foreign currency markets (Alsakka and ap Gwylim 2012a; Alsakka and ap Gwylim 2012b; Alsakka and ap Gwylim 2013; Tran et al 2019). Most of the above‐cited papers also showed spillovers to other countries, especially neighboring and emerging ones.…”
Section: Introductionmentioning
confidence: 99%